Sleep Clinical Record application in Brazilian children and its comparison with Italian children - Corrêa, Camila de Castro [UNESP]; Weber, Silke Anna Theresa [UNESP]; Evangelisti, Melania; Villa, Maria Pia (Elsevier, 2019)
Objective: To apply the Sleep Clinical Record (SCR) to a sample of Brazilian children with sleep complaints, to compare the results with Italian children, and to identify variables that influence phenotype. Methods: Brazilian and Italian children, 4–11 years of age and matched for age, gender, obesity, and apnea−hypopnea index and who presented with complaints related to sleep, were selected. The instrument used was the SCR, and the procedure used was full-night cardiorespiratory monitoring. Results: The sample consisted of 51 Brazilian children and 102 Italian children. Brazilian children presented with oral breathing (55%), tonsillar hypertrophy (69%), Friedman palate position (88%), malocclusion (84%), and OSAS score (Brouilette questionnaire) (55%). The SCR among obese Brazilian children was higher as compared to that in nonobese subjects (obese, 10.84 vs nonobese, 9.13; p = 0.03). In the comparison between Brazilian and Italian children, the total Brazilian SCR was higher than the Italian SCR score (Brazilian SCR, 10.21 ± 7.56; Italian SCR, 8.95 ± 2.55; p = 0.002). The Italian SCR score was influenced by obesity, whereas the Brazilian SCR was influenced by others symptoms (daytime sleepiness, enuresis, nocturnal choking, headache, limb movements). Conclusion: Brazilian children with sleep-disordered breathing show a higher SCR score as compared to Italian children. Obesity and tonsillar hypertrophy, Friedman palate position alteration, and dental malocclusion further influenced the total SCR score among Brazilian children. This may be due to access difficulties in Brazil where children should have more assistance to obtain medical care.
Keywords: Child; Diagnostic techniques and procedures; Obstructive; Questionnaire; Sleep apnea; Sleep Clinical Record